THE EFFECTIVENESS OF BODY-BALLET ON HEALTH AND MOTOR PLASTICITY OF GIRLS IN HIGH SCHOOL - Tatiana Vitalyevna Baksheva (Вестник Северо-Кавказского федерального университета)
This article analyzes the current trends in fitness dance styles. Described by means of a substantial component of classical dance and choreography in ballet body. Presented research tools morphological and functional indicators and the level of motor plasticity students.